Evaluation of critical success factor through HOT-FIT method for the implementation of e-KOlab (electronic consignation, franchise, organizational network) as a strategy to scale-up SMEs - Farida, Farida; Febrianty, Febrianty; Budilaksono, Sularso; Suryani, Ni Kadek; Gorda, A. A. A. Ngurah Tini Rusmini (Linguistics and Culture Review, 2021)
The purpose of this study is to evaluate the Critical Success Factors for the implementation of e-KOlab using the HOT-Fit approach so that indicators can be obtained that have a significant effect on the net benefits of the application for SMEs in Bali under the guidance of IWAPI Bali. The research sample is MSME actors under the guidance of IWAPI Bali who uses the e-Kolab application. MSMEs are spread across 9 regencies/cities, namely: Buleleng, Klungkung, Tabanan, Karangasem, Denpasar, Bangli, Badung, Jembrana, and Gianyar. Therefore, the sampling used the Saturated Sampling method so that there were 145 people who had indeed participated in the e-Kolab application testing and its utilization. The data analysis technique used in this study is SEM with the Variance or Component-Based (VB-SEM) approach with the PLS technique. The results of the Critical Success Factor evaluation through the HOT-FIT Method on the Implementation of e-KOlab as a strategy for SMEs to Scale Up indicate that there is a need for improvement in System quality, system use, the role of the Office, and the role of the Service. That is, 4 of the 13 hypotheses in this study were rejected.